Pengaruh Media Pembelajaran Berbasis Android terhadap Hasil Belajar Ranah Kognitif dan Afektif Siswa Kelas IV - Siti Mughimatun Ulya (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of android-based learning media on learning outcomes in the cognitive and affective domains of fourth grade students at SDN Pebatan 01. The method used was an experimental quantitative method in the form of a true experimental design with a posttest-only control design. There are two groups in this research design, namely the experimental class group that was given treatment and the control class group that was not treated. The research instrument used was a multiple choice test in the cognitive domain, in the affective domain using an observation sheet in the form of an observation sheet. The material used is the material for measuring the angle of charge of mathematics learning. The data analysis technique used is in the form of prerequisite test analysis and hypothesis testing with t-test. The results obtained in this study are (1) In the cognitive domain from the t-test results obtained sig <0.05 or 0.049 <0.05, so H0 is rejected and Ha is accepted. This means that the android-based learning model has an influence on learning outcomes in the cognitive domain: (2) Affective domain learning outcomes from the t-test results obtained a sig value of 0.002 < 0.05, which means that there is a difference or influence from the use of android-based learning media on affective domain learning outcomes. where H0 is rejected and Ha is accepted. So descriptively there is a difference or influence of android-based learning media on students' cognitive and affective learning outcomes, this is shown by the results obtained by students where the score in the experimental class is better than the control class.